2018
DOI: 10.1097/olq.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination and Infection Prevalence Among Men Who Have Sex With Men Who Travel Internationally

Abstract: Among men who have sex with men traveling internationally, self-reported hepatitis B virus (HBV) vaccination prevalence was 77% and less prevalent among older men and those with HBV infection. The HBV infection prevalence was 25% and was associated with older age and HIV infection. Testing for chronic infection, universal vaccination, and treatment for populations with multiple risks is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…The findings of our study indicated that most were not fully vaccinated, were unable to prove vaccination or were unaware of their vaccination status. These percentages were also lower than the vaccination rates reported in other studies conducted exclusively with MSM, which varied between 50.7% [13] and 77.4% [14], even with self-reporting [13] as the data collection method.…”
Section: Discussioncontrasting
confidence: 69%
“…The findings of our study indicated that most were not fully vaccinated, were unable to prove vaccination or were unaware of their vaccination status. These percentages were also lower than the vaccination rates reported in other studies conducted exclusively with MSM, which varied between 50.7% [13] and 77.4% [14], even with self-reporting [13] as the data collection method.…”
Section: Discussioncontrasting
confidence: 69%
“…Apart from one study, conducted as a case–control study, 53 all used a cross-sectional study design. All studies reported participant country of origin; 19 (59.4%) studies included travellers from multiple countries, 52–70 four (12.5%) from the UK, 54 , 58 , 69 , 71 three (9.4%) from the USA, 72–74 two (6.3%) from Sweden, 75 , 76 and one (3.1%) each from Finland, 77 Belgium, 51 Malta, 78 Canada, 79 Switzerland, 80 North Korea 81 and France. 82 The median age of the participants ranged from 21 73 to 45 59 years.…”
Section: Resultsmentioning
confidence: 99%
“…Although specific LGBTQ key words were included in our search, no studies targeting this marginalized community came out. Men who have sex with men are disproportionately at risk of sexual transmitted disease which makes them candidates for Hepatitis B and HPV vaccines [ 104 , 105 ]. Vaccines such as HPV address a sensitive topic, and pharmacists express discomfort discussing sexual health matters in a pharmacy setting [ 68 ].…”
Section: Discussionmentioning
confidence: 99%